THE PROBLEM OF DIGITAL INEQUALITY IN EDUCATION AND PEDAGOGICAL APPROACHES TO ELIMINATING IT (Universal International Scientific Journal, 2026)
This article provides a scientific analysis of the problem of digital inequality in the education system and the issues of eliminating it through pedagogical approaches. The article discusses in detail the main causes and consequences of digital inequality, ways to create equal opportunities using modern technologies and pedagogical methods. It also presents the decisions and practical measures of our President Shavkat Mirziyoyev in the field of education.
Keywords: digital inequality, education, pedagogical approach, innovative technologies, equal opportunities